2021
DOI: 10.3389/fpsyg.2021.716513
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash-Associated Disorders. Biopsychosocial Profiles of Pain Perception in Forensic Cases of Victims of Motor Vehicle Accidents

Abstract: In order to make a complete diagnosis of all the factors influencing whiplash associated disorders (WAD), the evidence suggests that the condition evaluation should follow an integrated biopsychosocial model. This perspective would offer a fuller view of it, recognizing the interplay between the medical, biomechanical, social, and psychological factors. Despite the progress made in the subject, evidence of which psychosocial factors influence the experience of pain in litigant WAD patients is limited. A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The systematic review found no studies evaluating the content validity of PROMs of Quality of Life in patients with WAD and very low-quality evidence for content validity based on reviewer ratings. Only 3 PROMs fulfilled criteria of having at least one study of internal structure in a WAD sample: the SF-36 total sum score, 24 the SF-6D, and the EQ-5D-3L. 25 The SF-36 total sum score is not a recommended approach.…”
Section: Quality-of-life Domainmentioning
confidence: 99%
“…The systematic review found no studies evaluating the content validity of PROMs of Quality of Life in patients with WAD and very low-quality evidence for content validity based on reviewer ratings. Only 3 PROMs fulfilled criteria of having at least one study of internal structure in a WAD sample: the SF-36 total sum score, 24 the SF-6D, and the EQ-5D-3L. 25 The SF-36 total sum score is not a recommended approach.…”
Section: Quality-of-life Domainmentioning
confidence: 99%
“…However, rear-end impacts are most common in injury statistics. Women are 1.5–3 times more prone to neck injuries than men [ 19 , 20 , 21 ]. It should be noted that in most modern cars, improved seat design is the dominant measure to enhance passenger protection against neck injuries in rear-end collisions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple sources of information for the assessment of symptom validity, as well as self-report measures, can be especially effective in WAD, as it is compatible with the biopsychosocial model of the disease (Campbell et al, 2018;Pina et al, 2021;Sterling, 2011). Pain and other psychosocial variables, such as anxiety, depression, perception of disability, alteration in the quality of life, or attitude toward the illness situation play a major role in the development of WAD (Björsenius et al, 2020;Campbell et al, 2018;Sterling, 2011).…”
mentioning
confidence: 99%